The impact of enhanced creditor rights on venture capital: Evidence from the Uniform Fraudulent Transfer Act - Megginson, William L.; Park, Hyeonjoon (Journal of Corporate Finance, 2025)
This study investigates how the Uniform Fraudulent Transfer Act (UFTA) shapes venture capital (VC) investment strategies and startup outcomes. Using data on 34,578 VC-backed startups from 1977 to 2019, we find that the UFTA inadvertently leads VC investors to prioritize existing portfolio companies over new investments, resulting in longer funding durations. Startups subsequently rely more heavily on secured debt and experience diminished innovation outcomes. Additionally, under heightened financial pressure, startups commit violations more frequently, particularly employment-related offenses. Nonetheless, startups backed by more experienced VCs demonstrate stronger innovation performance and are more likely to achieve successful exits through initial public offerings.